Young and the urban in Addis Ababa: towards a popular history of the 1974 Ethiopian revolution, c. 1950s-1974 - Asfaw, Semeneh Ayalew (Department of Political Studies, 2022)
This is a study about the Ethiopian revolution through the social and cultural developments that formed the Ethiopian capital, Addis Ababa. The largest participants in the social protests of 1974 were predominantly young Addis Ababans with a range of class and social formations. They were the authors of the Ethiopian revolution. In addition to documenting the social protests of 1974, however, this study is also interested in tracing the subject formation of the youth in Addis Ababa between the 1950s and 1974. By giving special focus to developments in the post 1950 period, where demographic, social and cultural transformations take particular intensity and form in the making of Addis Ababa, this study seeks to expose the linkages between the subject formation of the youth in the two and a half decades leading up to the revolution. By examining the processes that went into the formation of dissidence, this study asks whether factors (other than university student militancy) were significant to explain the emergence of the Ethiopian revolution. The material for this study comes from three main archives: 1. Non-literary works: newspapers and magazines; 2. Literary works: mainly novels and musical productions; and 3. Interviews. By integrating written and audio-visual archives and oral materials, this study examines and analyses the history of subject formation of the youth before and during the Ethiopian revolution. The significance of this study lies in its emphasis on the multiplicity of social actors in the making of the Ethiopian revolution as well as its attempt to demonstrate that subject formation was a function of everyday life and social and cultural production of rebel sensibility in Addis Ababa. In its attempt towards writing the popular dimensions of the history of the Ethiopian revolution in the Ethiopian capital, this study examines the conditions in which the social protests of 1974 occurred, and the social and cultural context in which the revolution became "thinkable". It demonstrates the interconnections between the social and cultural formation of subjects, the political formativeness of cultural phenomena, and explicitly political protest.